2016
DOI: 10.1002/acs.2679
|View full text |Cite
|
Sign up to set email alerts
|

Robust hybrid estimation and rejection of multi‐frequency signals

Abstract: SUMMARYWe consider the problem of output regulation for LTI systems in the presence of unknown exosystems. The only a priori knowledge about the exosystem consists in the fact that it generates multi-frequency signals, while the number and the value of the frequencies are not known. The control scheme relies on two main components: an estimation algorithm, to reconstruct the signal generated by the exosystem, and a controller, to enforce the output regulation property to the closed-loop system. To tackle the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Suppose that conditions (9) hold for P 0 . Then there existsε > 0 such that any P ∈ F ε with ε ∈ (0,ε) satisfies (9).…”
Section: Structural Conditions For Output Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppose that conditions (9) hold for P 0 . Then there existsε > 0 such that any P ∈ F ε with ε ∈ (0,ε) satisfies (9).…”
Section: Structural Conditions For Output Regulationmentioning
confidence: 99%
“…The conditions(9) are formulated for a system of the form proposed in (8) for simplicity. Nonetheless, it can be easily shown that P 0 in (3) satisfies such conditions if and only if the plant transformed via (6), (7) satisfies(9).…”
mentioning
confidence: 99%
“…Another important problem in adaptive control is the one dealing with unknown disturbance rejection, often referred to as “adaptive regulation.”) Indeed, in these works, the plant's model is known or identified, but the disturbance model is unknown or uncertain. In the direct adaptive methods, adaptive filters are used to tune the feedback controller (for example, via adaptive observers of the disturbance) to reject the unknown disturbance, without explicitly estimating its model.…”
Section: Model‐based Adaptive Controlmentioning
confidence: 99%
“…In particular, [26] presents a simplified global stability analysis by using contraction theory rather than traditional Lyapunov analysis; and, on the other hand, [28] proposes a hybrid observer to identify the n frequencies from a multi-frequency signal with saturated amplitudes. Recently, the effectiveness of the hybrid observer in the presence of poorly sampled signal is shown in [29].…”
Section: Introductionmentioning
confidence: 99%